Glaucoma Diagnostic Capability of Global and Regional Measurements of Isolated Ganglion Cell Layer and Inner Plexiform Layer. Issue 3 (March 2017) - Chien, Jason L.; Ghassibi, Mark P.; Patthanathamrongkasem, Thipnapa; Abumasmah, Ramiz; Rosman, Michael S.; Skaat, Alon; Tello, Celso; Liebmann, Jeffrey M.; Ritch, Robert; Park, Sung Chul
Abstract : Purpose: To compare glaucoma diagnostic capability of global/regional macular layer parameters in different-sized grids. Materials and Methods: Serial horizontal spectral-domain optical coherence tomography scans of macula were obtained. Automated macular grids with diameters of 3, 3.45, and 6 mm were used. For each grid, 10 parameters (total volume; average thicknesses in 9 regions) were obtained for 5 layers: macular retinal nerve fiber layer (mRNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), ganglion cell-inner plexiform layer (GCIPL; GCL+IPL), and ganglion cell complex (GCC; mRNFL+GCL+IPL). Results: Sixty-nine normal eyes (69 subjects) and 87 glaucomatous eyes (87 patients) were included. For the total volume parameter, the area under the receiver operating characteristic curves (AUCs) in 6-mm grid were larger than the AUCs in 3- and 3.45-mm grids for GCL, GCC, GCIPL, and mRNFL (all P <0.020). For the average thickness parameters, the best AUC in 6-mm grid (T2 region for GCL, IPL, and GCIPL; I2 region for mRNFL and GCC) was greater than the best AUC in 3-mm grid for GCL, GCC, and mRNFL ( P <0.045). The AUC of GCL volume (0.920) was similar to those of GCC (0.920) and GCIPL (0.909) volume. The AUC of GCL T2 region thickness (0.942) was similar to those of GCC I2 region (0.942) and GCIPL T2 region (0.934) thickness. Conclusions: Isolated macular GCL appears to be as good as GCC and GCIPL in glaucoma diagnosis, while IPL does not. Larger macular grids may be better at detecting glaucoma. Each layer has a characteristic region with the best glaucoma diagnostic capability.